Reference guide to English morphology - Bauer, Laurie; Lieber, Rochelle (Oxford, 2015)
Includes bibliographical references and index
Keywords: Grammar, Comparative and general -- Morphology -- Terminology; Ngữ pháp, so sánh -- Hình thái học -- Thuật ngữ; Grammar, Comparative and general -- Word formation; Ngữ pháp, so sánh -- Hình thành từ